Using agricultural demand for reducing costs of renewable energy integration - Tarun M. Khanna (ZBW – Leibniz Information Centre for Economics, 2021)
While demand response is recognized as a useful tool for integrating renewable electricity, the related literature in developing countries has been limited due to lack of data on end-use load profiles. Meanwhile, even though the water-energy-nexus in developing countries is well researched, the value of agricultural pumping load as a demand-side resource to the power system has been ignored. This article fills the gap by collecting agricultural load data from two distribution utilities in the Indian state of Gujarat and using it in a mixed-integer linear programming model to estimate the flexibility provided by agricultural load control to the power system. Using a flexible load representation, the model chooses the optimal periods for agricultural supply subject to the constraints of meeting the irrigation needs of farmers, given the marginal cost of electricity. The model estimates that agricultural load control already reduces total system costs by 5% or USD 6.26 per MWh of agricultural consumption in the current power system. Going forward, with high shares of solar generation, shifting agricultural demand to daytime hours aids system flexibility. It reduces renewables curtailment by 4–7%; limits cycling costs of coal power plants; and reduces marginal integration costs by 21%. Deploying decentralized solar irrigation pumps instead of large-scale solar power plants enables higher absorption of peak solar generation and reduces costs further. Since these costs are disproportionately borne by end consumers, improving system flexibility also improves consumer welfare.
Keywords: 330; Demand side management; Power system modelling; Renewable energy integration; Load control